2009
DOI: 10.1002/app.30983
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and sorption studies of dyes through PVA cryogel membranes

Abstract: The capacity of poly(vinyl alcohol) (PVA) to crosslink through freeze/thaw method was used to obtain PVA hydrogel membranes (HG) that were subjected to sorption and diffusion experiments using three dyes: Congo red (CR), methylthymol blue (MTB), and crystal violet (CV). To study the sorption of dyes into the cryogenic membrane, dye solutions at different concentrations were used. After sorption, desorption of dyes from the PVA membrane was monitored to quantify the possible regeneration of the membrane (PVA HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…However, polymer/AC composites with macroporous matrices produced by cryogelation have not been practically studied using dye adsorption [107]. Papancea et al [190] studied sorption and diffusion of three dyes: Congo red, methylthymol blue (MTB), and crystal violet (CV) through PVA membrane. After sorption, the dye-release kinetics (desorption) from the PVA membrane was monitored to evaluate regeneration of the membrane.…”
Section: Equilibrium and Kinetic Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, polymer/AC composites with macroporous matrices produced by cryogelation have not been practically studied using dye adsorption [107]. Papancea et al [190] studied sorption and diffusion of three dyes: Congo red, methylthymol blue (MTB), and crystal violet (CV) through PVA membrane. After sorption, the dye-release kinetics (desorption) from the PVA membrane was monitored to evaluate regeneration of the membrane.…”
Section: Equilibrium and Kinetic Adsorptionmentioning
confidence: 99%
“…The diffusion experiments revealed that CR and MTB do not permeate the PVA membrane making it a promising candidate in the advanced purification of wastewaters. The effect of the incorporation of dyes on chemical properties of PVA cryogels was studied using DSC, SEM, and FTIR spectroscopy [190].…”
Section: Equilibrium and Kinetic Adsorptionmentioning
confidence: 99%
“…Permeability of heavy metal ion salts through PVA HG membranes was measured using a diffusion cell similar to that reported elsewhere 26, 27. This consists of two 250 mL compartments filled with electrolyte solution (the donor compartment) and water (the receptor compartment).…”
Section: Methodsmentioning
confidence: 99%
“…According to the analysis, this action was due to the large number of polar groups in GO, which occurred due to the hydrogen bonds in GO, SA, and AKP. [27][28][29] These hydrogen bonds absorbed within a certain wave-number range. 30,31 To explore and regulate the effect of the hydrogen bonds in the SA-AKP composite system after different mass fractions of GO were added, the broad peak at 3000-3700 cm 21 was smoothed, and the peak area ratio (i.e., the ratio of different types of hydrogen bonds) was calculated after we subtracted the straight line and the Gauss peak fitting of the peak analyzer.…”
Section: Mechanical Propertiesmentioning
confidence: 99%